Dystonia and Writer's Cramp Triggered by Exercise - J Gordon Millichap (Pediatric Neurology Briefs Publishers, 1997)
An 11-year-old girl with a gait disturbance and foot dystonia, especially after exertion at the end of the day, and handwriting difficulty with cramps after a short school exercise, was evaluated at the Neuropaediatric Unit, CHUV, Lausanne, Switzerland.